Comparison of physical activity assessed using hip- and wrist-worn accelerometers - Kamada, Masamitsu; Shiroma, Eric J; Harris, Tamara B; Lee, I-Min (Gait & posture, 2016)
•Physical activity can be assessed using accelerometers worn at the hip or wrist.•In adults, few data exist on how estimates from both sites compare.•We found that physical activity correlates moderately well between the two sites.•The most and least active subjects were more likely to be identically classified. It is unclear how physical activity estimates differ when assessed using hip- vs wrist-worn accelerometers. The objective of this study was to compare physical activity assessed by hip- and wrist-worn accelerometers in free-living older women. A cross-sectional study collecting data in free-living environment. Participants were from the Women's Health Study, in which an ancillary study is objectively measuring physical activity using accelerometers (ActiGraph GT3X+). We analyzed data from 94 women (mean (SD) age=71.9 (6.0) years) who wore a hip-worn and wrist-worn accelerometers simultaneously for 7 days. Using triaxial data (vector magnitude, VM), total activity volume (counts per day) between the two locations was moderately correlated (Spearman's r=0.73). Hip and wrist monitors wear locations identically classified 71% individuals who were at the highest 40% or lowest 40% of their respective distributions. Similar patterns and slightly stronger agreements were observed when examining steps instead of VM counts. Accelerometer-assessed physical activity using hip- vs wrist-worn devices was moderately correlated in older, free-living women. However, further research needs to be conducted to examine comparisons of specific activities or physical activity intensity levels.